2009
DOI: 10.1042/cs20080394
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic perspectives for the role of inflammation in diabetic nephropathy

Abstract: Diabetes and its complications have become a public health problem. One of the most important complications is diabetic nephropathy, which is nowadays the main cause of chronic renal failure. In spite of our greater understanding of this complication, the intimate mechanisms leading to the development and progression of renal injury are not well understood. New perspectives in activated innate immunity and inflammation appear to be relevant factors in the pathogenesis of diabetes. Moreover, different inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
183
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(186 citation statements)
references
References 176 publications
2
183
0
1
Order By: Relevance
“…Inflammation increases expression of TF, and TF induces inflammation (14). It also is well known that diabetes leads to inflammation and fibrosis (15,16). We therefore studied the renal expression of inflammatory and fibrogenic genes (Fig.…”
Section: Survival Of F1 (B6 × 129) Heterozygous Enosmentioning
confidence: 99%
“…Inflammation increases expression of TF, and TF induces inflammation (14). It also is well known that diabetes leads to inflammation and fibrosis (15,16). We therefore studied the renal expression of inflammatory and fibrogenic genes (Fig.…”
Section: Survival Of F1 (B6 × 129) Heterozygous Enosmentioning
confidence: 99%
“…In this line, higher serum HMGB1 levels have been reported in individuals with coronary heart disease (17,18) or heart failure (19) compared with those without these diseases. Inflammation is involved in the development of diabetic nephropathy (20), and in this line, a recent study showed that HMGB1 may play a role in the development of diabetic nephropathy in rats (21).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Later, the role of inflammation and inflammatory cytokines in DN was studied over the last few years. [10][11][12][13][14][15][16] Inflammation secondary to ischemia and endothelial dysfunction was found to be associated with the development of DN. [17][18][19] Some medications were found to slow down the progression of DN through suggested antiinflammatory actions.…”
Section: Introductionmentioning
confidence: 99%